Role of serial ultrasound screening of venous thrombosis in oncologic children with central lines - Paola Previtali; Stefania Paladini; Lucia Gandini; Maria Chiara Allemano; Carlo Morosi; Veronica Biassoni; Jacopo Colombo; Elena Tagliabue; Daniela Codazzi (Elsevier, 2019)
Objective: Pediatric oncology patients are more likely to develop venous thromboembolic events related to central venous catheter (CVC). Study aim was to determine the incidence of catheter related thrombosis (CRT) in a cohort of pediatric oncology patients using vascular ultrasound (US). Methods: Consecutive children of a single cancer referral center, requiring medium to long term CVC implantation, were screened for CRT, using serial ultrasound exams. Measurements and main results: US examinations were taken 15, 30 and 90 days after CVC implantation. A total of 113 catheters were studied in 103 patients (median age 10.5 years old). Ultrasound screening was completed in 80.5% patients. Apart from three subjects, US investigations were well tolerated. Patients were followed for a median of 87 days. No symptomatic CRT was recorded throughout. Three cases of asymptomatic thrombosis were identified with early US screening; incidence of CRT events for 1000 catheter-days was 0.11. The presence of previous catheter-related infection and an history of one or more previous CVC placement were identified as risk factors. Conclusions: In our pediatric patients the incidence of CRT is low. Ultrasound monitoring is well tolerated and allows detecting asymptomatic CRT. Patients with previous CVC infection or insertion seem to have a higher risk of CRT (p =0.003 and p = 0.043 respectively). Keywords: Central venous catheters, Venous thrombosis, Vascular ultrasound, Vascular catheter infections, Children